ORAL TRADITION AND EARLY HISTORY OF EFON ALAAYE, SOUTHWEST NIGERIA - Adeoti, Ezekiel Oladele (European Scientific Journal, ESJ, 2013)
This paper is an outline history of Efon Alaaye, Southwest Nigeria. The origin and early history of Efon, like those of most Yoruba towns, due to the eaucity of written accounts is frosty. However, much evidence point to a certain group, the Isinkin under their leader called Oisikin, as the earliest settler, but later dislodged by another group, the Obalu led by Ekuwi Oloba. Efon Alaaye kingdom was eventually established after the Aaye group from Ile-Ife had supplanted the Obalu. The prime purpose of this essay is to shed more light upon the pre-colonial history of Efon Alaaye. The work seeks to conduct an incisive inquiry into the origin, establishment and early political history of the town. The study adopts the descriptive and analytical method of historical discourse as the framework of analysis.